2018
DOI: 10.4328/jcam.5464
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder following childbirth: a study of prevalence and related factors in Iranian women

Abstract: Aim: Women who experience severe distress during the process of childbirth might develop Post-Traumatic Stress Disorder (PTSD) with feeling the danger of death or severe trauma for the mother or the infant. Considering the changes in the diagnostic criteria of traumatic birth from the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) to DSM-V and the adverse consequences of PTSD following childbirth, the present study was conducted. infant's restlessness (OR=3.04, 95%CI: 1.39-6.64,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In a systematic review and meta-analysis in 2017, the overall prevalence of this complication worldwide was reported to be 4% on average [16]. In several limited Iranian research, this complication's prevalence 26.7% [7], [7], and 20%, respectively [24]. Notably, the prevalence of this complication in Iran is relatively higher than in other countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a systematic review and meta-analysis in 2017, the overall prevalence of this complication worldwide was reported to be 4% on average [16]. In several limited Iranian research, this complication's prevalence 26.7% [7], [7], and 20%, respectively [24]. Notably, the prevalence of this complication in Iran is relatively higher than in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in this research, some demographic features (age, education level, low socioeconomic status, access to health insurance, culture, & religion) were also considered factors influencing PTSD probability [34]. Mousaviet al considered the variables of income level, pregnancy intention, pregnancy complications, kind of delivery, analgesia, and conformity between the common type of delivery and actual delivery efficiency in treating PTSD [7]. In the research, King et al indicated that three variables of instrumental utilization in vaginal delivery, observed low level of immunity via labor and low level of spousal support during childbirth, had a significant relation with PTSD [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PTSD can develop following a difficult or traumatic birth during which women think they or their baby might die or be seriously injured (Yildiz et al, 2017). Mokhtari et al (2018) demonstrated a significant relationship between birth satisfaction, perceived support during and after childbirth, and PTSD following childbirth. In terms of specific aspects of birth satisfaction, studies showed that perceived loss of control during labour and childbirth, receiving inadequate and insufficient support from medical staff and partner, invasive obstetric interventions, such as emergency caesarean section and instrumental vaginal childbirth, were significantly associated with increased risk for traumatic birth and developing PTSD (Ayers et al, 2016;Hollander et al, 2017;Reed et al, 2017).…”
mentioning
confidence: 99%